The Association of Losartan and Ramipril Therapy With Kidney and Cardiovascular Outcomes in Patients With Chronic Kidney Disease: A Chinese Nation-Wide Cohort Study in Taiwan. Issue 48 (December 2015) - Hsing, Shih-Chun; Lu, Kuo-Cheng; Sun, Chien-An; Chien, Wu-Chien; Chung, Chi-Hsiang; Kao, Sen-Yeong
Abstract : Abstract: The aim of this nation-wide cohort study was to assess the association of using an angiotensin-converting enzyme inhibitor (ACEi) or angiotensin II receptor blocker (ARB) therapy on the prognosis of hypertensive patients with chronic kidney disease (CKD). We used Cox's proportional hazard regression model to estimate hazard ratios (HRs) for the risk of end-stage renal disease (ESRD), all-cause mortality, cardiovascular mortality, and first hospitalization for cardiovascular disease (CVD) for losartan and ramipril versus conventional antihypertensive agents. In total, 136, 266 hypertensive patients with CKD in Taiwan were followed up from 2001 to 2008. In an average follow-up of 5.9 years, 7364 (5.40%) patients reached ESRD, 4165 (3.06%) patients died, and 6163 (4.52%) patients had their first hospitalization for CVD. Use of losartan or ramipril was associated with a lower risk of the endpoints compared with the conventional group. In the losartan group, the risks of ESRD, all- and cardiovascular-cause mortality, and first hospitalization for CVD were decreased by 9.2% ( P  = 0.01), 24.6% ( P  < 0.001), 12.4% ( P  = 0.03), and 36.0% ( P  = 0.01), respectively. In the ramipril group, these risks decreased by 7.6% ( P  = 0.02) for ESRD, 56.9% ( P  < 0.001) for all-cause mortality, 7.5% ( P  = 0.04) for cardiovascular mortality, and 24.7% ( P  < 0.001) for first hospitalization. This study indicated that losartan and ramipril had distinct association on the prognosis of hypertensive patients with CKD, and was first to disclose that the mean time to reach each endpoint for patients in the losartan, ramipril, and conventional group was not significantly different. However, further study is needed to confirm results of the present study.